Diagnosis and Location of Power Cable Faults Based on Characteristic Frequencies of Impedance Spectroscopy - Gen Li; Jie Chen; Hongze Li; Libin Hu; Wenjun Zhou; Chengke Zhou; Mingzhen Li (Energies, 2022)
Power cable condition diagnosis and deterioration location rely on signatures of aging characteristics which precede the final breakdown. The purpose of this study was to investigate how to diagnose and locate the aging and/or deterioration of power cables through the analysis of the impedance spectroscopy. The concepts of the reference frequency and characteristic frequency of cable impedance spectroscopy are defined for the first time. Based on the reference frequency, the optimal frequency range for analysis of impedance spectroscopy can be determined, whilst based on characteristic frequency, a set of criteria for assessing cable conditions are examined and established. The solution proposed in this paper has the advantage of being easier to implement than the previously reported “broadband” impedance spectroscopy methods, as it helps to reduce the frequency range for measurement instrumentations; the proposed method also does not need the measurements of the parameters of the cable being tested.